A música dos pampas em uma perspectiva lexical : milongando entre o espanhol e o português - Santos, Odair José Silva dos (My University, 2015)
In the scenario of Rio Grande do Sul State that was for many years the scene of disputes, with border lines that enabled mobile linguistic and cultural-exchange, Gaucho's songs (local music) can be characterized as major productions to reveal facts of culture that endure for centuries and which were shaped, constructed and reconstructed in and through history. In this process, the lexicon assumes a key role, since it is through a specific lexicon (or regional) that there is identification and cultural elements ressignification. Divided into four chapters, this dissertation intends to investigate the loanwords from Spanish into Portuguese, from linguistic and cultural contact on the borders of Brazil/Argentina/Brazil and Uruguay, identified in songs performed by the duo of singers and composers César Oliveira e Rogério Melo. The research carried out has shown the presence of bilingualism in border regions of Rio Grande do Sul, exemplified in the lyrics of the songs analyzed, in which the lexicon employed exerts specific directions, often mythological. Therefore, we can conclude that there is a universe of symbolic representations of this border community themselves, here revealed through Gaúcho‟s songs.
No cenário do Rio Grande do Sul - Estado que foi por longos anos palco de disputas, com linhas fronteiriças móveis que possibilitaram o intercâmbio linguístico e cultural -, as canções gauchescas podem ser caracterizadas como importantes produções para revelar fatos de cultura que perduram há séculos e que foram moldados, construídos e reconstruídos na e pela história. Nesse processo, o léxico assume um papel essencial, uma vez que é por meio de um léxico específico (ou regional) que há a identificação e a ressignificação dos elementos culturais. Dividida em quatro capítulos, esta dissertação pretende investigar os empréstimos linguísticos da Língua Espanhola para a Língua Portuguesa, a partir do contato linguísticocultural nas fronteiras de Brasil/Argentina e Brasil/Uruguai, identificados em canções interpretadas pela dupla de cantores e compositores César Oliveira e Rogério Melo. A pesquisa encetada permitiu constatar a presença de bilinguismo nas regiões limítrofes do Rio Grande do Sul, exemplificado nas letras das canções analisadas, nas quais o léxico empregado exerce sentidos específicos, muitas vezes mitológicos. Pode-se assim concluir que existe um universo de representações simbólicas próprias dessa comunidade de fronteira, aqui revelados por meio das canções gauchescas.
Keywords: Lexicologia; Música sul-rio-grandense; Bilinguismo; Lexicology; Music South Rio Grande; Bilingualism